Rethinking Contextual Waste Management Policies to Mitigate the Risk of Antimicrobial Resistant Infections in Healthcare Settings: Evidence from Selected Hospitals in West Cameroon - , Willite Ngankou Tchapda, Josué Simo Louokdom, Patrick Mbopi Yamen, O’Neal Dorsel Youté, Jean Jacques Tchouani Kouemo, Roméo-Gabin Tchotcheu Seugnou, Michelle Cleone Taffo, Leonel Browndon Tchatchouang Tchiasso, Emmanuel Haddison Sako, Pierre René Fotsing Kwetche (Archives of Current Research International, 2025)
Background: In large numbers of low- and middle-income countries, hospital waste management policies are conducted below the minimum standards due to resource scarcity. In these areas, accumulated wastes often represent potent sources of microbial populations that may evolve as health threats to humans’, animals’ and environmental health, further exacerbating poverty. Data from accumulated waste and/or its surrounding environment can therefore help to redefine, reorient and optimize waste management policies for the healthcare setting users’ safety. Objective: The aim of this cross-sectional study was to investigate the type, the diversity, the load and the drug susceptibility trends of bacteria populations that grow in the vicinity of solid waste accumulation sites in four healthcare facilities of the Ndé division, West Cameroon. Methods: Soil and air specimens were collected for bacterial screening at varying distances from the solid waste accumulation sites. Culture, isolation, identification, enumeration and susceptibility tests on bacteria isolates were performed according to standard protocols. Results: Relevant findings revealed diversified populations made up of 53 bacterial groups including Staphylococcus spp. (50.94%), Gram-positive rods (26.42%), Acinetobacter spp. (11.32%), Klebsiella spp. (7.55%), Serratia spp. and Pseudomonas spp. (1.89% each). In terms of their loads, Gram-negative rods loads were higher than those observed with other morphological types. Further details indicated higher loads and diversities in soil specimens collected in the vicinity of solid waste accumulation sites. These trends in loads and diversity were particularly obvious in one of the four target healthcare institutions. The susceptibility tests revealed multidrug resistance, with the highest rates recorded against beta-lactam antibiotics. The most effective drugs consisted of Gentamicin, Clindamycin, Erythromycin, and Trimethoprim/Sulfamethoxazole. Conclusion: These findings are indications that exposed human populations are at risk of contracting resistant bacteria, with a higher likelihood in the vicinity of accumulated wastes in all settings. Accordingly, contextual implementation of hospital hygiene policies in line with biosafety and biosecurity was suggested as a priority to meet the expectations of the 1st, 3rd and 4th United Nations Sustainable Development Goals.